2009
DOI: 10.1007/s10457-009-9245-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant water relations and edaphoclimatic conditions affecting acorn production in a holm oak (Quercus ilex L. ssp. ballota) open woodland

Abstract: Acorn production patterns and the annual evolution of water relations parameters of Quercus ilex ssp. ballota (Desf.) Samp. in a dehesa (an open woodland forest) subject to various soil treatments (ploughing, ploughing ? sowing, control) were studied in southwest Spain from June 2006 to December 2008. The effects of soil water holding capacity and effective soil depth on soil and plant water status and acorn production were also investigated. Water parameters showed significant differences between the ploughin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 52 publications
2
25
1
Order By: Relevance
“…Soil water depletion in mid summer may have a negative effect on early acorn ripening and, ultimately, on acorn yield (Carevic et al 2010). At the sites in this study, Rolo and Moreno (2011) reported a worsening of hydric status of trees growing among Retama by the end of summer, explained by the high spatial overlap of Q. ilex and deep Retama roots .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Soil water depletion in mid summer may have a negative effect on early acorn ripening and, ultimately, on acorn yield (Carevic et al 2010). At the sites in this study, Rolo and Moreno (2011) reported a worsening of hydric status of trees growing among Retama by the end of summer, explained by the high spatial overlap of Q. ilex and deep Retama roots .…”
Section: Discussionmentioning
confidence: 58%
“…It is hypothesised that the contrasting rooting profiles of Cistus and Retama determined these differences. Carevic et al (2010) observed a close relationship between acorn productivity and the physiological state of oak trees. At the sites in the present study, the physiological status of scattered Q. ilex trees was monitored over three consecutive summers (Rolo and Moreno 2011).…”
Section: Discussionmentioning
confidence: 86%
“…Summer water shortage is already a primary limiting factor for tree growth, seed production, and seedling recruitment in these regions (Carevic et al 2010;Castro et al 2005;Espelta et al 2008). Therefore, future increases in aridity will likely cause profound changes in the structure and composition of Mediterranean-type forests, especially where the water demand of the dominant species is already marginally met (Bréda et al 2006;Breshears et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it appears that physiological traits in plants can be used as predictors of other traits. For example, previous research in Mediterranean ecosystems found that low xylem water potential and a decrease in cuticular transpiration during summer months limited acorn production in Quercus ilex stands during autumn (Alejano et al, 2008;Carevic et al, 2010). Similarly, Moriana et al (2007) concluded that water relations in drought-induced olive trees in a semiarid habitat had an effect on the concentration of phenolic compounds in the oil they produced.…”
Section: Plant Water Relations As a Predictive Toolsmentioning
confidence: 97%